MODEL PENGEMBANGAN PENDIDIKAN KARAKTER BERBASIS PENGUATAN BUDAYA SEKOLAH RELIGIUS DI SMA ISLAM SULTAN AGUNG 3 SEMARANG - Anwar, Khoirul; Choeroni, Choeroni (Universitas Islam Sultan Agung, 2019)
The problem of national identity and character lately is at risk. The number of negative events and behaviors, both individually and in groups in the community, illustrates the degadration of the nation's moral values. The character crisis is characterized by an increasing number in crime and violence in the society, including in the world of education. This fact encourages the emergence of various lawsuits on the effectiveness of character education in schools which so far have been seen by some communities as having failed in building students' affection with eternal values and being able to answer the challenges of the changing times.That the crisis of character, one of which is caused by a lack of understanding and practice of religious teachings. Religious characters that require students to understand and be able to practice the teachings of their religion become one of the most important character points in order to improve the good character of students. Religious becomes the foundation of the nation's character, so we need a way to build religious character for each student. Departing from this, in this article the author will discuss about the development model of religious school culture-based character education. The problem in this article will be focused first, on how to develop character education models based on the strengthening of religious school culture in Sultan Agung 3 Islamic High School Semarang; second, how the results of the implementation of the development of character education based on strengthening the culture of religious schools in Sultan Agung 3 Islamic High School Semarang. This article is the result of a qualitative descriptive study conducted by the author at Sultan Agung 3 Islamic Senior High School Semarang. From the research conducted by the author, the results of this research are: the model of character education development based on strengthening the religious school culture is needed in order to increase the effectiveness of character education in schools.Â Keywords: Character education, character crisis, religious school culture.Â